Advancing Trypanosoma cruzi N-myristoyltransferase as a drug target for Chagas disease through in silico discovery and biochemical evaluation - González García, Diana; Torres, Angel; Talevi, Alan; Alberca, Lucas N.; Beltran, Miguel A.; Lara, Frida; Da Silva Ferreira, Marina; Farani, Priscila S. G.; Almeida, Igor C.; Maldonado, Rosa A. (Frontiers in Molecular Biosciences, 2026)
IntroductionN-myristoylation is a crucial lipid modification that governs protein localization, intracellular trafficking, and function in eukaryotic cells. The enzyme N-myristoyltransferase (NMT), which catalyzes this modification, has emerged as an attractive drug target for parasitic diseases. In this study, we performed a comprehensive biochemical and antiparasitic evaluation of Trypanosoma cruzi NMT (TcNMT), utilizing novel “in silico–identified inhibitors” to assess its potential as a therapeutic agent for Chagas disease.MethodsRecombinant TcNMT was cloned, expressed, and purified for enzymatic characterization. Catalytic activity and substrate affinity were evaluated using a fluorescence-based assay. Four in-silico-selected NMT inhibitors were screened for (i) enzyme inhibition, (ii) cytotoxicity in human cardiomyocytes, and (iii) antiparasitic activity in T. cruzi–infected cardiomyocytes. QUINE and the reference inhibitor DDD85646 were further characterized by calculating selectivity indices. Proteomic profiling of myristoylated proteins was conducted in amastigotes and trypomastigotes following treatment with DDD85646 to identify pathway-level effects.ResultsAll recombinant TcNMT preparations were catalytically active and displayed high affinity for peptide substrates. Among the screened compounds, QUINE showed moderate antiparasitic efficacy but very low cytotoxicity, yielding a high selectivity index (SI = 28.11). In contrast, DDD85646 exhibited greater antiparasitic potency but substantially higher host-cell toxicity (SI = 4.67). Proteomic analysis of DDD85646-treated parasites revealed downregulation of myristoylated proteins in both life stages, including ARF GTPases and enzymes associated with vesicular trafficking and lipid metabolism. Host cell proteomes remained largely unchanged.DiscussionBiochemical characterization and phenotypic testing support TcNMT as a viable therapeutic target for Chagas disease. QUINE demonstrates the most favorable pharmacological profile, combining antiparasitic activity with excellent selectivity and low host toxicity, making it a strong lead candidate for future drug optimization. Proteomics data indicate that NMT inhibition disrupts critical pathways required for parasite viability yet spares host cellular machinery, reinforcing the mechanistic selectivity of TcNMT targeting. Further studies are warranted to improve potency and evaluate in vivo efficacy.